IMPACT OF JIKUMERASA VILLAGE TOURISM DEVELOPMENT ON COMMUNITY STRUCTURE AND DISTRIBUTION PATTERNS BIVALVIA, GASTROPODE AND ECHINOIDEA - Ismail, Irwan; Irsan, Irsan; Kasmawati, Kasmawati (Program Studi Pendidikan Biologi FKIP Unpatti, 2022)
Background: Jikumerasa village has the main object of marine and beach tourism in Buru Regency. This activity has the potential to have a negative impact on community structure and distribution patterns of Bivalves, Gastropods and Echinoidea. Methods: The study was carried out in August 2022 - September 2022. Sampling used a transect measuring 1 x 1 m (1 m2). Physical and chemical parameters of the waters were measured temperature, pH and salinity. Results: There were 16 types of gastropods, 9 types of Bivalves and 3 types of Echinoidea found at the study site. Low species density and diversity. High uniformity and no dominant type. A total of 17 species had random distribution and 7 species clustered. Water temperature 29.30C - 29.60C, pH 6.3 - 6.6 and Salinity 250/00 - 300/00. Conclusion: Beach tourism in Jikumerasa Village has an impact on community structure and distribution patterns of Bivalves, Gastropods and Echinoidea. This can be seen from the few species found, low density and diversity, high uniformity, mostly random distribution patterns of species, and conditions of pH and salinity of the waters below the quality standard.